GEOSPATIAL ANALYSIS OF FLOOD HAZARD IN MUARA KELINGI DISTRICT (Prodi Fisika FST UNJA, 2026)
Muara Kelingi District, Musi Rawas Regency, is one of the areas that has experienced frequent flood events due to its geographical condition, which is located near major river systems. This study aims to analyze the level of flood hazard in Muara Kelingi District based on the physical characteristics of the area. The method employed is spatial analysis based on a Geographic Information System (GIS) using an overlay technique in ArcGIS software. Several parameters were analyzed, including rainfall, land use, slope, river density, and soil type. Rainfall data were analyzed using the Thiessen Polygon method, while the other parameters were obtained from DEMNAS, the revised Spatial Plan (RTRW) of Musi Rawas Regency, and the Tanah Air Indonesia geodatabase. Each parameter was assessed using a scoring and weighting approach to generate a flood hazard index. The results indicate that the majority of Muara Kelingi District falls into the moderate flood hazard category, covering 93.89% of the area, while the high hazard category accounts for 2.94% and the low hazard category covers 3.16%. Areas with high flood hazard are generally located in lowland areas close to river channels, characterized by relatively flat slopes and dominated by built-up land use that reduces the soil’s infiltration capacity. In addition, the dominance of Haplic Podsolic soils with moderate to low infiltration capacity also contributes to the potential for surface water accumulation. The findings of this study are expected to serve as a basis for risk-based spatial planning and flood disaster mitigation efforts in Muara Kelingi District